Gambaran Culture Standards China melalui Perspektif Orang Indonesia dalam Kelompok Kerja Indonesia-China - Ellys Tjo (Fakultas Psikologi Universitas Pancasila, 2009)
The purpose of this paper is to show that Chinese (mainland) culture standards within Indonesian-Chinese intercultural work team relationship needed to be understood by Indonesian workers as diverse culture similarities, differences, and overlapping often become the conflict foundations. Anticipation and solution are required since the issues frequently lead the intercultural work group into culture shock, target failures, psychological stress. As a result, the individual, group, and/or organization productivity declines. By qualitative approach, using culture standards method from Prof. Dr. Alexander Thomas, five Indonesian workers from Indonesian-Chinese work groups are selected through criterion sampling. From 39 critical incidents produced, ten Chinese cultural standards from Indonesian perpective are built as follows: (1) national pride or patriotism; (2) mianzi or face; (3) customs; (4) quanxi or importance of social network; (5) duty; (6) hierarchical order; (7) cost-effectiveness; (8) collectivism; (9) conflict avoidance; and (10) mistrust. This finding has to be identified as integrated values, and is not to be generalized far and wide in the consideration of Chinese multiculturalism. Three coping strategies-planning, empathy, and assertiveness are generated from this research and could be applied in the efforts of achieving intercultural work group success and synergy.